An Analysis Of India’s Trade Performance With SAARC Countries In 21st Century (International Journal of Food and Nutritional Sciences, 2022)
In today's world no nation exists in economic isolation. Driven towards integration by the pressure of economic interest of the region, seven South Asian countries- Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka formed the South Asian Association for Regional Cooperation (SAARC) in 1985. The SAARC comprises eight countries of South Asia is a manifestation of the determination of their people of south Asia to work together towards finding solutions to their common problem in a spirit of friendship, trust and understanding and to create an order based on mutual respect, equity and share benefits. The primary objective of the association is the acceleration of the process of economic and social development in member states, through collective action in agreed areas cooperation. The main objective of this paper is to study the trade performance of India with SAARC countries. In simple terms it is proved that in recent time the general trend is that India does more exports and imports with Bangladesh followed by Nepal and Sri Lanka comes the third in terms of value, there seem to be an interesting turnaround from 2000-01, where Bangladesh (export) while Nepal (Import) comes first followed by Sri Lanka (export) while Bangladesh (Import) and then comes Pakistan (both). This trend of India’s trade with the selected SAARC countries reflects the present period, but this may change over time. Overall data, share and growth rate seems very attractive but actually last seven years, it increased with low rate. From 2000-01 to 2006-07, bilateral trade has been increasing trend but after that it has fluctuated many times such that 2008 to 2010, 2015-16 and 2019-2022. India must find out new innovative products and export them to different countries SAARC to become a renowned and prosperous nation in future.